Estimation of net accumulation and removal of fluorescent dissolved organic matter in different Baltic Sea water masses - Terzić, Elena; Zabłocka, Monika; Loginova, Alexandra N.; Borzycka, Karolina; Kowalczuk, Piotr (Frontiers in Marine Science, 2024)
This study aimed to detect non-conservative processes which affect fluorescent dissolved organic matter (FDOM) distribution in the Baltic Sea. An extensive data set comprised of 408 FDOM data, optical and physical profiles and the development of a water masses balance model enabled to ascertain the sources of mixing anomalies. These were seen as second-order deviations in FDOM distribution as a function of salinity in three layers: surface water, Baltic Sea Winter Water and deep water. The difference between modelled and measured FDOM values at three different excitation/emission wavelengths enabled to show the strength of non-conservative processes, such as photochemical and microbial decomposition (negative residual values) or dissolved organic matter extracellular release from phytoplankton, heterotrophic uptake and release from anoxic sediments (positive residual values). Humic-like FDOM fractions displayed positive residuals in all seasons for intermediate and deep layers and negative residuals in surface waters. Largest accumulation rates of humic-like fractions were reached in the Gulf of Gda ńsk during summer at intermediate and deep layers, while greatest removal was observed in surface waters during spring in Bornholm and Gotland Basins and summer in the Gulf of Gdańsk, likely due to photodegradation. Positive residuals of the protein-like fraction were seen during summer and autumn in the Gulf of Gda ńsk at the surface, likely linked to phytoplankton abundance and stemming also from low molecular weight by-products of humic-like components' photodegradation. Spatial transects revealed an increase in humic-like residuals with depth and a strong correlation with apparent oxygen utilization, increasing with higher fluorescence and exhibiting an asymptotic trend. A relationship was found between the protein-like fractions and phytoplankton biomass proxies. A generalized concept for FDOM cycling in the Baltic was proposed, highlighting photobleaching as the dominating non-linear process that determines the efficiency of the humic-like FDOM removal. The protein-like component was seen to be more efficiently taken up by aerobic prokaryotes at the surface. Microbial utilization and reworking of organic matter, release from sediments and a decade long stagnation of bottom water masses, all contribute to the observed accumulation of FDOM in mesohaline deep waters below the permanent pycnocline in the Baltic Sea.